Cross-cultural similarities in reasoning about personal continuity in reincarnation: evidence from South India. Issue 2 (2nd April 2016) - White, Claire
Abstract : Ethnographic reports suggest the cross-cultural recurrence of practices designed to determine who has returned to the human world through the process of reincarnation. This paper attempts to explain these trends by cross-culturally replicating experiments originally conducted in the US with participants from mixed-religious affiliations to Jains in South India. In a series of imaginative perspective-taking tasks, Jain adults reasoned about the likelihood of different people to be the reincarnation of a deceased person based on similar features between the two. Participants endorsed a concept of reincarnation as entailing a bodily change from death to rebirth. Nevertheless, in the tasks, they reasoned as though physical marks and episodic memories were superior cues to identifying reincarnated people as compared to other similarities, including other physical and mnemonic features. These decisions were heightened when the distinctiveness of the features was increased and thus the probability of another living person sharing that feature decreased. Together, these studies replicate and extend findings with US adults to suggest that such reasoning is not simply the product of cultural input and suggest a role for mundane processes of person recognition in the recurrence of reincarnation concepts and associated practices cross-culturally.